2020
DOI: 10.1371/journal.pone.0234843
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of radioactive iodine ablation for patients with intermediate-risk papillary thyroid cancer

Abstract: Background The beneficial effects of radioactive iodine (RAI) ablation for intermediate-risk papillary thyroid cancer (PTC) patients are still controversial. Materials and methods To determine the impact of RAI therapy on disease-specific survival (DSS) in patients with intermediate-risk PTC, we retrospectively analyzed the data of 23107 intermediate-risk PTC patients who underwent primary thyroidectomy with or without RAI in the Surveillance, Epidemiology, and End Results (SEER) database. Results RAI therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 30 publications
(33 reference statements)
3
34
0
Order By: Relevance
“…Giving RAI in intermediate-risk PTC has been a subject of controversy. On the one hand, studies have shown that RAI therapy could reduce recurrence and hence should be considered in intermediate-risk PTC patients [21,40], whereas others have suggested that RAI ablation may not have a beneficial role in decreasing the risk of recurrence in intermediate-risk PTC patients [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Giving RAI in intermediate-risk PTC has been a subject of controversy. On the one hand, studies have shown that RAI therapy could reduce recurrence and hence should be considered in intermediate-risk PTC patients [21,40], whereas others have suggested that RAI ablation may not have a beneficial role in decreasing the risk of recurrence in intermediate-risk PTC patients [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The single study that assessed recurrence used three different methods (AMES [Age, Metastasis, Extracapsular tumor, Size], MACIS [Metastases, Age, Completeness of resection, Invasion, Size], and De Groot); we combined the results and reversed the outcomes because recurrence and survival are not going in the same line. Two of the included studies showed a negative effect of RAI on outcomes [ 8 , 11 ], three showed a beneficial effect [ 3 , 12 , 13 ], and the remaining two were neutral [ 14 , 15 ]. The fixed effect was used due to the substantial heterogeneity (I2=93%; p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, they suggested beneficial effects of RAI remnant ablation in loco-regional recurrence (relative risk: 0.31; 95% CI: 0.2-0.49) and distant metastases (absolute decrease in risk: 3%; 95% CI: -0.01 to 0.04). In our meta-analysis, six of seven recent studies, of which five were adjusted [ 3 , 12 - 15 ], examined survival rate. Our results are in agreement with Sawka et al’s results regarding the benefits of RAI use in remnant ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive iodine (RAI) therapy is an integral part of the standard care for differentiated thyroid cancer (DTC) [1]. For DTC patients with intermediate or high risk of recurrence following total thyroidectomy, RAI ablation therapy is recommended [2][3][4]. Moreover, when 131 I used is more than 1.22 GBq (33 mCi) for RAI therapy, which is equivalent to a dose limit of >5mSv, several days of hospitalization in a licensed facility is mandatory [5,6].…”
Section: Introductionmentioning
confidence: 99%